Improving the Reliability of Web Search Results - Pereira, Tiago Filipe Roque (2017)
Over the last years, it has been possible to observe the exponential growth of the internet. Everyday new websites are created. Everyday new technologies are developed. Everyday new data is added into the web. The search for available online data on the web has become an increasingly common practice to any person because, the regular user wants to know more. For any existing question or doubt, the user wants the answer the fastest way possible. It is in this field where the search engines are an exceptional tool in helping their users. In order to aid the users reach for what they were seeking for, search engines have become a fantastic tool. Either it is searched for a certain website, some specific information or even for the seek of knowledge, search engines help the user reach his goal. Without their existence, it would be much more difficult and frustrating to find the needed information, which would lead to a tremendous loss of time and resources, and most of the cases, the user would probably not reach the results it was looking for. Thus, the development of web search engines provided a better comfort for the user. However, despite the fact there is a really effective tool, sometimes it can lead to unintended results. Towards a search, the search engine can lead to a suggestion of a website that does not correspond to the expectation of the user. This is due to the fact that search engines only show part of the content related with each correspondent hyperlink, which for several times, users think the answer for what they are looking for is in some website and when they start analysing it, the intended information is not there. Entering and leaving different websites, can be a big inconvenience, even more if the internet connection is slow (as it can happen outside the big cities or in least developed areas), which makes the user lose more time and patience. This dissertation intends to explore the possibility and prove the concept that, with the help and junction of different technologies such as parsing, web crawling, web mining and semantic web in a machine, it is possible to improve the reliability from the search engines, in order for the user lose the minimal time or resources possible.